Age Matters: Key Contributors to Interferon Toxicity in Infants During Influenza Virus Infection - Abigail P. Onufer; Alison J. Carey (Viruses, 2025)
Respiratory viral infections are a leading cause of early childhood hospitalizations in the United States. Neonatal immune responses are reliant on innate mechanisms during the first few months of life. Interferons (IFNs) are a key component of this response. These antiviral cytokines are produced early in infection and aid in viral control and clearance. Although generally considered protective in the setting of respiratory viral infections, the recent literature has suggested that IFNs may exacerbate disease. In the process of promoting an antiviral environment, IFNs impede cell proliferation, contribute to pulmonary barrier disruption, and generate reactive oxygen species. This is not tolerated in the rapidly developing neonatal lung. Therefore, IFNs contribute to pathogenesis in the influenza-infected neonate. This review focuses on the potential mechanisms that drive IFN-induced toxicity in neonates and prospective therapeutics to mitigate this toxicity.